Thermal evaporation synthesis of vertically aligned zn2sno4/zno radial heterostructured nanowires array - Han, Gillsang; Kang, Minje; Jeong, Yoojae; Lee, Sangwook; Cho, Insun (Nanomaterials, 2021)
The construction of a heterostructured nanowires array allows the simultaneous manipula-tion of the interfacial, surface, charge transport, and transfer properties, offering new opportunities to achieve multi-functionality for various applications. Herein, we developed facile thermal evaporation and post-annealing method to synthesize ternary-Zn2SnO4/binary-ZnO radially heterostructured nanowires array (HNA). Vertically aligned ZnO nanowires array (3.5 µm in length) were grown on a ZnO-nanoparticle-seeded, fluorine-doped tin oxide substrate by a hydrothermal method. Sub-sequently, the amorphous layer consisting of Zn-Sn-O complex was uniformly deposited on the surface of the ZnO nanowires via the thermal evaporation of the Zn and Sn powder mixture in vacuum, followed by post-annealing at 550◦C in air to oxidize and crystallize the Zn2SnO4 shell layer. The use of a powder mixture composed of elemental Zn and Sn (rather than oxides and carbon mixture) as an evaporation source ensures high vapor pressure at a low temperature (e.g., 700◦C) during thermal evaporation. The morphology, microstructure, and charge-transport properties of the Zn2SnO4/ZnO HNA were investigated by scanning electron microscopy, X-ray diffraction, Raman spectroscopy, transmission electron microscopy, and electrochemical impedance spectroscopy. Notably, the optimally synthesized Zn2SnO4/ZnO HNA shows an intimate interface, high surface roughness, and superior charge-separation and-transport properties compared with the pristine ZnO nanowires array.
Keywords: Charge transport; Heterostructured nanowires array; Inter-face; Thermal evaporation synthesis; Zn2SnO4/ZnO